Ultrafine intralath precipitation of V(C, N) in 12Cr-1MoWV (wt.%) ferritic/martensitic steel. (May 2021) - Rietema, C.J.; Hassan, M.M.; Anderoglu, O.; Eftink, B.P.; Saleh, T.A.; Maloy, S.A.; Clarke, A.J.; Clarke, K.D.
Abstract: 12Cr-1MoWV (wt.%) ferritic/martensitic (F/M) steel is a candidate material for fuel cladding in advanced nuclear reactors. As such, understanding the relationship between microstructure and mechanical properties in the context of irradiation environments for these steels is critical. Here we reveal the presence of ultrafine scale (2-5 nm), intralath V(C, N) precipitates in conventionally heat treated 12Cr-1MoWV steel for the first time. Lower N content results in finer intralath precipitates, whereas higher N content results in larger, elongated disks or needles. N content significantly alters the strength, but not the strain hardening behavior, by its impact on precipitate characteristics. Finer precipitates could have an impact on irradiated behavior, specifically their capacity as defect sinks. The presence of ultrafine scale V(C, N) precipitates in conventionally heat treated 12Cr-1MoWV steel, controlled by N variations, provides a new means for tailoring the strength and irradiation response of F/M steels for nuclear applications. Graphical abstract: Image, graphical abstract